Rationalizing Public Transport System of Dhaka City: Proposal of Creating a Multimodal Hierarchical Transport Network to Reduce Traffic Congestion - Niger, Maher (Nakhara : Journal of Environmental Design and Planning, 2019)
The concept of rationalization can be defined as a structured process to increase effectiveness through a maximize use of existing resources. Rationalization in terms of road infrastructure or systems can be achieved in various ways; establishing hierarchy of routes, optimize bus-stop points with density distribution changes, proper integration of motorized and non-motorized transport and providing policy framework. In the highly densely populated city of Dhaka, rationalizing public transport is one way to minimize the mismatch between demand and supply. This paper is concerned with the following issues: providing a general description of the city transport system, identifying problems and demands analysis in the area of study area; studying the rationalization of public transport, particularly public transport system design (routes and their categorization) and proposing the creation of a multimodal hierarchical transport network for Dhaka. The findings suggest establishing a major component, a hierarchal-network. Beside establishing network hierarchy, rationalizing is also interdependent upon system planning, institutional framework, organization and financing, terminal locations, public-private relationships, government roles, policies, service integration, and the management of public transport. This is can be accomplished by all stakeholders sharing the relative success and failure, depending different levels of each components’ performances. The findings of this paper will help planners and decision makers to optimize the investment in the transport infrastructure.